Staff shortages and inappropriate work conditions as a challenge geriatrics and contemporary healthcare service at large faces - Pruszyński, Jacek; Cianciara, Dorota; Pruszyńska, Irena; Włodarczyk-Pruszyńska, Inga (Journal of Education, Health and Sport, 2022)
Deficit of human resources in health care is a widespread problem occurring not only in Polish system. Demanding work, emotional stresses and insufficient support are often associated with the doctor's shift mode of work and an excess of duties combined with a shortage of time allocated to their performance. It can be assumed that most of the doctors intend to continue their work so far, but its negative features may in the future affect their decisions about choosing a different career path, especially if the shortage of medical personnel increases. This may further overburden doctors (especially young doctors) with excess working hours, reduce the quality of their activities, increase the chances of committing an unintended medical error related to exhaustion, and lead to functional burnout. This situation may lead to a renewed intensification of economic emigration to other countries, both in the EU and outside the EU, which create more favourable working conditions for working life. The scale of the problem is exacerbated by the increasing health needs of the aging population, causing an increasing burden on the health care sector, both in the near and distant future. This can create a vicious cycle where increasing burdens will drain physicians out of public health system, and increase the burden put on remaining physicians. The resulting restriction of access to medical services will lead to the deterioration of the health condition of the Polish population. In order to prevent such a situation, it would be necessary to increase the motivation to remain both in the medical profession and at work in Poland through actions aimed at improving working conditions and strengthening the sense of occupational safety of doctors. These activities should be especially aimed at group of medics starting their professional lives.